(untitled) (Research, Society and Development, 2022)
Hyaluronidase is an enzyme responsible for the degradation of hyaluronic acid, which, when applied in a way that generates adverse effects, must be used. The objective of this article was to carry out a narrative review of the literature on the use of hyaluronidase in orofacial harmonization, to present its indications, contraindications, as well as its level of effectiveness. Searches were carried out in scientific databases (PubMed and Google Scholar) and included literature reviews, case reports and clinical studies published between 2016 and 2021, in English and Portuguese. It was concluded that, within the scope of orofacial harmonization, hyaluronidase is indicated for the management of complications related to hyaluronic acid fillers. It is effective in the management of mild or severe complications, and can be applied in the treatment of hematomas, nodules, granulomas, foreign body reactions and inflammatory reactions, as well as for vascular complications such as tissue necrosis and livedo reticularis. Its use is contraindicated in case of hypersensitivity to its components. Side effects caused by hyaluronidase are rare and involve allergic reaction and local itching.